The blue book of Nebo - Steffan Ros, Manon (Deep Vellum Publishing, 2021)
"Winner of the 2018 National Eisteddfod Prose Medal and the 2019 Llyfr y Flwyddyn (Wales Book of the Year) After nuclear disaster, Rowenna and her young son, Dylan, are among the rare survivors in rural northwest Wales. Left alone in their isolated hillside cottage, after others have died or abandoned the towns and villages, they must learn new skills in order to remain alive. With no electricity or modern technology they must return to the old ways of living off the land, developing new personal resources. While they become more skilled and stronger, the relationship between mother and son changes in subtle ways, as Dylan must take on adult responsibilities, especially once his baby sister Mona arrives. Despite their close understanding, mother and son have their own secrets, which emerge as in turn they jot down their thoughts and memories in a found notebook. As each reflects on their old life and the events since the disaster which has brought normal, twenty-first century life to an end, their new-found maturity and sense of purpose contrast not only with their old selves but also with new emotional challenges when Mona sickens and dies. In this touching prize-winning and best-selling new novel, Manon Steffan Ros not only explores the human capacity to find new strengths when faced with the need to survive, but also questions the structures and norms of the contemporary world"--